Assessment of Heart Attack Management and Awareness Among Non-Medical Subjects - Ghafoor, Ayesha; Iqbal, Fakeha; Ali, Syed Hani; Tahir, Mahnoor; Tahir, Umar; Dawood, Muhammad; Qamar, Khadija (Pakistan Armed Forces Medical Journal, 2024)
Objective: The objective of this study was to assess the awareness level of heart attack and its management among nonmedical students. Methodology: It was a cross sectional study and took place from Mar to Apr 2022. 301 non-medical consenting students (aged 16-25 years) responded to our online questionnaire, and their responses were compared to standard answers to estimate awareness. This data was analysed using SPSS version 25.1 Results: 49(16.3 %) students were male and 252(83.7 %) were females. 265(88 %) of the participants were aware of the term heart attack. 211(70 %) showed good knowledge of risk factors for heart attack. Conclusion: Overall, the subjects showed a good knowledge of heart attack symptoms and risk factors. There was however little awareness about emergency management in case of heart attack.